Early NT-ProBNP (N-Terminal Probrain Natriuretic Peptide) Elevation Predicts Malignant Edema and Death After Reperfusion Therapy in Acute Ischemic Stroke Patients. Issue 2 (February 2021) - Zhang, Xuting; Yan, Shenqiang; Zhong, Wansi; Yu, Yannan; Lou, Min
Abstract : Background and Purpose: We aimed to investigate the relationship between early NT-proBNP (N-terminal probrain natriuretic peptide) and all-cause death in patients receiving reperfusion therapy, including intravenous thrombolysis and endovascular thrombectomy (EVT). Methods: This study included 1039 acute ischemic stroke patients with early NT-proBNP data at 2 hours after the beginning of alteplase infusion for those with intravenous thrombolysis only or immediately at the end of EVT for those with EVT. We performed natural log transformation for NT-proBNP (Ln(NT-proBNP)). Malignant brain edema was ascertained by using the SITS-MOST (Safe Implementation of Thrombolysis in Stroke-Monitoring Study) criteria. Results: Median serum NT-proBNP level was 349 pg/mL (interquartile range, 89–1250 pg/mL). One hundred twenty-one (11.6%) patients died. Malignant edema was observed in 78 (7.5%) patients. Ln(NT-proBNP) was independently associated with 3-month mortality in patients with intravenous thrombolysis only (odds ratio, 1.465 [95% CI, 1.169–1.836]; P =0.001) and in those receiving EVT (odds ratio, 1.563 [95% CI, 1.139–2.145]; P =0.006). The elevation of Ln(NT-proBNP) was also independently associated with malignant edema in patients with intravenous thrombolysis only (odds ratio, 1.334 [95% CI, 1.020–1.745]; P =0.036), and in those with EVT (odds ratio, 1.455 [95% CI, 1.057–2.003]; P =0.022). Conclusions: An early increase in NT-proBNP levels was related to malignant edema and stroke mortality after reperfusion therapy. Abstract : Supplemental Digital Content is available in the text.